2022
DOI: 10.4081/hls.2022.10806
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of errors during susceptibility reporting of glycopeptide antibiotics for enterococcal isolates on sole basis of widely used disk diffusion test

Abstract: In resource limited settings, very often susceptibility reports glycopeptide antibiotics are released only on the basis of disk diffusion test. Determination of MIC by either E-strips or microbroth dilution tests can be of paramount importance in checking the errors that may have incurred with the singular use of disk diffusion tests. Distribution of errors in Vancomycin and Teicoplanin susceptibility reporting by disk diffusion test was evaluated in comparison with MIC determination with reference method of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One limitation of this study is that the disc diffusion assay has been reported to be relatively insensitive and, in some cases, inaccurate [52]. In particular, the disc diffusion assay for vancomycin is prone to significant errors, prompting the CLSI recommendation that MIC testing follow disc diffusion screens to differentiate vancomycin-susceptible from vancomycin-intermediate isolates [31,53]. Similarly, the disc diffusion assay for colistin is error-prone due to poor diffusion into agar, and currently, no standard disc diffusion assay for colistin exists [54].…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study is that the disc diffusion assay has been reported to be relatively insensitive and, in some cases, inaccurate [52]. In particular, the disc diffusion assay for vancomycin is prone to significant errors, prompting the CLSI recommendation that MIC testing follow disc diffusion screens to differentiate vancomycin-susceptible from vancomycin-intermediate isolates [31,53]. Similarly, the disc diffusion assay for colistin is error-prone due to poor diffusion into agar, and currently, no standard disc diffusion assay for colistin exists [54].…”
Section: Discussionmentioning
confidence: 99%